Synergistic Combination of Exogenous Hormones to Improve the Spawning and Post-spawning Survival of Female Yellow Catfish - Hu, Weihua; Huang, Peipei; Xiong, Yang; Guo, Wenjie; Wang, Yuhong; Fan, Qixue; Wang, Qingyun; Mei, Jie (Frontiers in Genetics, 2020)
Multiple repeat spawners make large contributions to long-term population stability and aquaculture breeding programs. A high percentage of female yellow catfish (Pelteobagrus fulvidraco) died for spawning failure or incomplete spawning after artificial spawning by traditional synthetic hormones including human chorionic gonadotropin (hCG), luteinizing hormone releasing hormone (LHRH) and domperidone (DOM). The present study was designed to compare the efficacy of different combinations of exogenous hormones for inducing ovulation in yellow catfish using hCG, LHRH, DOM and carp pituitary extraction (CPE). We found a optimal strategy for exogenous hormones administration, the mixture of LHRH/CPE for the first injection and LHRH/CPE/DOM for the second injection, could greatly improve the rates of spawning success, weight of spawned eggs and survival rate after spawning. Interestingly, a population of female yellow catfish with defective reproductive duct could not spawn and showed high mortality after induced by a combination of hCG/LHRH/DOM, whereas a synergistic combination of hCG, LHRH, DOM and CPE could efficiently induce spawning and reduce mortality in the defective yellow catfish, in which a significant decrease of Vitellin and E2 levels. Altogether, our findings provide an effective combination of exogenous hormones to improve spawning and post-spawning survival of female yellow catfish.